2006
DOI: 10.1159/000094530
|View full text |Cite
|
Sign up to set email alerts
|

Weight Lifting and Aortic Dissection: More Evidence for a Connection

Abstract: Background/Aims: In 2003, we reported on a small number of patients in whom acute aortic dissection appeared to be causally related to intense weight lifting. If additional cases could be identified, the phenomenon of weight lifting induced aortic dissection would be further substantiated. We now report a substantially larger number of cases in which aortic dissection is associated with intense physical exertion. Methods: Additional cases of acute aortic dissection occurring at the time of intense physical exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(116 citation statements)
references
References 10 publications
(6 reference statements)
4
107
0
5
Order By: Relevance
“…117) Hatzaras et al pointed out the relationship between aortic dissection and weight lifting, in which systolic blood pressure is markedly elevated. 118) An abrupt elevation of blood pressure may lead to a tear of intima, although there has been no literature which clearly demonstrated a direct relationship of blood pressure variation and incidence of aortic dissection. Hatzaras reported that 65 of 90 patients with aortic dissection (72%) could recall specific inciting events, exertional or emotional, immediately prior to the onset of dissection.…”
Section: Preventionmentioning
confidence: 99%
“…117) Hatzaras et al pointed out the relationship between aortic dissection and weight lifting, in which systolic blood pressure is markedly elevated. 118) An abrupt elevation of blood pressure may lead to a tear of intima, although there has been no literature which clearly demonstrated a direct relationship of blood pressure variation and incidence of aortic dissection. Hatzaras reported that 65 of 90 patients with aortic dissection (72%) could recall specific inciting events, exertional or emotional, immediately prior to the onset of dissection.…”
Section: Preventionmentioning
confidence: 99%
“…Some specific sports activities, including weight lifting, can trigger the onset of AAD due to a rapid increase in hemodynamic stress. 11) In these cases, the underlying cause is a sportsinduced mechanism. Driving a vehicle is probably not directly related to the pathogenesis of AAD.…”
Section: Discussionmentioning
confidence: 99%
“…However, BP rises rapidly and remarkably during high-intensity leg press exercise (10). Indeed, it has been reported the accidents, such as artery dissociation and subarachnoid hemorrhage, occur during resistance exercise (39)(40)(41)(42). Therefore, care should be taken regarding the rapid and marked increases in BP response to resistance exercise, particularly in middle-aged and older men.…”
Section: Discussionmentioning
confidence: 99%